(untitled) (ENTHYMEMA, 2012)
Metaphor is a cognitively complex device, based on the mapping of two conflicting domains and predominant in every dimension of daily life. The current neuroscientific perspective allows us today to recognise in the metaphoric thinking not only an activator of the brain’s plasticity – and as such an active participant in the evolutionary history of the human mind –, but also a further level of cognitive elaboration compared to the implicit mappings of metonymy.